Sagot :
Réponse :
2. Développe et réduis les expressions C, D et E :
C = 3(x + 7) = 3 x + 21
D = -5( 8 x – 2)= - 40 x+10
E = 9 x (-1 + 6 x ) = -9 x + 54 x²
3. Factorise les expressions F, G et H :
F = 5x + 15 = 5 (x+3)
G = 21 x² - 7 x = 7 x (3 x -1)
H = -45 y² - 36 y + 9 = 9 ( -5 y² - 4 y +1 )
Explications étape par étape
Bonsoir,
2)
C = 3(x + 7)
C = 3x + 21
D = -5(8x - 2)
D = -40x + 10
E = 9x(-1 + 6x)
E = -9x + 54x²
3)
F = 5x + 15
F = 5(x + 3)
G = 21x² - 7x
G = 7x(3x - 1)
H = -45y² - 36y + 9
H = 9(-5y² - 4y + 1)